Pemodelan cerdas disain meja belajar sederhana: Analisis material dengan finite element approach - Ameliyana Rizky Syamara Putri Akhmad Yani; Muhammad Alfin Abdurachim Putra (BKS-TM Indonesia, 2025)
This study analyzes the strength of study tables using the Finite Element Analysis (FEA) method and explores material variations, including very low-density PE plastic, Ductile iron, and balsa wood. The main focus of this study is on three-dimensional modeling and load-test simulations of 3000 N using a standard fixed-geometry fixture10. The simulation results show that Ductile iron exhibited the minimum deformation (0.051 mm), while balsa wood recorded the second largest (2.070 mm). However, a Factor of Safety (FS) analysis of 1.03 proves that balsa wood possesses adequate strength and a superior strength-to-weight ratio, making it the optimal choice. This study provides important insights into selecting optimal materials for designing sturdy, durable study tables that deliver maximum performance in everyday use.